Tempo de jejum e intensidade de sede na parturiente : estudo transversal - Godoy, Rafael Silva (2022)
To evaluate the fasting time of parturients and its association with thirst intensity. Methods: Parturients admitted for cesarean or vaginal delivery, between 18–40 years and at full-term pregnancy, were included. We recorded the time of last ingestion of food and liquids before delivery. A visual analog scale was used to assess thirst intensity. The main outcome was prepartum fasting time for solids (categorized at: 0–6 h, 6.1–11.9 h, and ≥ 12 h) and for liquids (categorized at: 0– 2 h, 2.1–6 h, 6.1–11.9 h, and ≥ 12 h). The second outcome variable was how the fasting time for solid and liquid was associated with reported thirst intensity. Results: In total, 297 cases were evaluated. Patients had a median age of 26 years and median parity of 2. Cesarean delivery (53.5%) was more frequent than normal delivery (46.5%). The mean ± standard deviation fasting time was 11.0 ± 5.9h for solids and 6.6 ± 5.7h for liquids. The cesarean section group had a longer fasting time for both solids and liquids. Thirst intensity was 4.4 times higher in patients with prolonged solids fasting (odds ratio 4.45; 95% confidence interval: 3.70–5.20; p < 0.001) and almost 5 times higher for fluid fasting (odds ratio 4.99; 95% confidence interval: 4.46–5.53; p < 0.001). Conclusions: The fasting time of parturients in antepartum was prolonged and thirst intensity increased with fasting length, and also, was higher in patients undergoing a cesarean section.